UPAYA MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN ANAK USIA 5-6 TAHUN MELALUI KEGIATAN BODY PAINTINGDI KELAS B2 TK TUNAS BANGSA SIAK SRI INDRAPURA - Hastuti, Desi; Wilson, Wilson; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Beginning writing skills of children aged 5-6 years is low, somechildren are not able yet to write the letter symbols are known, have not been able tomimic the letter, and have not been able to write his own name. The purpose of thisstudy was to determine whether there is an increased ability to write the beginning of achild through body painting and to find out how improvement occurs. The method usedin this study is the observation sheet form. The number of subjects in this study were 16children consisting of 6 boys and 10 girls. Based on the analysis of the assessmentprocess 2 cycles increased. The increase in the amount of 88.4%.Key Words: Writing Ability Starters